Unconstitutionality of the income tax calculation when offsetting foreign taxes with regard to the exemption of the subsistence minimum? A quantitative analysis - Thomas Kollruss (Heliyon)
The present study addresses a previously unexamined question of whether the calculation of income tax in the case of foreign tax credits violates constitutional law. Methodologically, this is investigated via quantitative analysis. As part of a quantitative analysis it is shown that the current method of calculating income tax when offsetting foreign taxes violates constitutional law in the form of the subjective net principle, as the taxpayer loses part of the tax-effective basic allowance deduction due to the calculation method; thus, the minimum subsistence level is no longer fully exempt from taxation with income tax. To address this issue, this study proposes a quantitative approach to calculating income tax, which allows for the calculation of income tax in the country of residence in accordance with the constitution when foreign taxes are offset. This method effectively and completely exempts the taxpayer's minimum subsistence level from income taxation. States can use this approach as a guideline to organise their income tax calculation in line with constitutional law.